Remains of sculptures kept in a makeshift storehouse - Temples of India Project Team (Jio Institute, 2024)
There are remains of several sculptures kept in a makeshift storehouse to the south of the Neelkanth Mahadev Temple. These have wall sculptures, lintels, pillar remnants, and other architectural elements. Noteworthy among these loose fragments is an image of Yogeshwar Vishnu or Vishnu sitting in the padmasana (lotus pedestal) yoga posture.